Morphocultural variants of Septoria tritici isolates - Cordo, Cristina Alicia (1997)
This is a morphocultural study under in vitro and in vivo condition on some Septoria tritici variants mainly originated from isolates collected from cultivars bearing Bobwhite 'S' and Kavkaz germplasm. The objective was to show the variability in cultural and morphobiometrical characters of atypical isolates (variants) derived from these germplasms and discuss the relationship with the pathogen’s adaptative process. The isolates were grown on potato dextrosa agar and studies with the optical and scanning electron microscope were performed. The thallus behaviour and the vegetative structures were described. It was confirmed that these atypical structures belong the S. tritici thallus. Under in vivo condition the isolates developed typical leaf blotch lesions with normal pycnidia. These contained cylindrical cells or pycnidiospores smaller than spores of the wild type . Possible reasons for the origin of these variants of S. tritici are considered.